Axial – Shear interaction on CLT hold-down connections – Experimental investigation. (1st April 2018) - Pozza, Luca; Ferracuti, Barbara; Massari, Milena; Savoia, Marco
Highlights: Tension-shear interaction in hold-down was never investigated until now. Results from a specifically designed experimental campaign are presented. Experimental results has been analysed using specific linearization criteria. Results allow to outline tension – shear interaction in hold-down connections. Dissipative capacity of hold-down connection has been extensively investigated. Abstract: Nowadays, the design of CLT wall connections is based on the hypothesis that hold-down connections are subjected only to tension and angle-brackets only to shear. Nevertheless, experimental investigations on CLT walls under seismic action highlighted that hold-downs may be subjected also to significant lateral displacement, and then to a tension-shear coupled action. The aim of this work is to experimentally investigate the axial-shear interaction in typical hold-down connections. To this purpose, an extensive experimental campaign was conducted with a specific setup allowing to impose prescribed levels of lateral displacement and varying the axial displacement in a monotonic or cyclic way. The test results on 15 specimens are presented here and critically discussed in terms of load–displacement curves, strength, stiffness, energy dissipation, strength degradation and ductility. Moreover, two different approaches for the definition of the connection's yielding limit are used, according to a tri-linear approximation of the experimental load–displacement curve. Forces and stiffnesses provided by these methods are compared with those predicted by code provisions.